Simultaneous Detection of Mycobacterium bovis and Mycobacterium tuberculosis in Human Cerebrospinal Fluid - Ritacco, Viviana (2007)
Fil: Ritacco, Viviana. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.